Water rights and multiple water uses: framework and application to Kirindi Oya irrigation system, Sri Lanka - Meinzen-Dick, Ruth S.; Bakker, Margaretha (International Food Policy Research Institute, 2000)
The growing attention to water rights in recent years reflects the increasing scarcity and competition for this vital resource. Because rights are at the heart of any water allocation system, they are also critical for any reallocation. Not only efficiency, but also fundamental issues of equity are at stake. To understand water rights requires going beyond formal statutory law (which may or may not be followed), to look at the many bases for claiming water. Because of the vital nature of this resource, state law, religious law, customary law and local norms all have something to say in defining water rights. The delineation of water rights is further complicated when we take into consideration multiple uses (irrigation, domestic, fishing, livestock, industries, etc.) as well as multiple users (different villages, groups of farmers in the head and tail, fishermen, cattle owners, etc.) of the resource. These overlapping uses bring in different government agencies, as well as different sets of norms and rules related to water. This paper provides a framework for examining the statutory and customary water rights of multiple users of water and applies it in the Kirindi Oya irrigation system in Sri Lanka, based on a multidisciplinary study conducted in 1997-1998. It demonstrates that the range of stakeholders with an interest in water resources of an irrigation system go far beyond the owners and cultivators of irrigated fields. As such, these groups are not only claimants on the ongoing management of water resource systems, but also need to be included in any considerations of transferring water from irrigation to other uses.